Specialist nurse initiated interventions in breast cancer care: A systematic review of randomised controlled trials. Issue 13 (14th April 2020) - Hussain Rawther, Shejila Chillakunnel; Pai, Mamatha Shivananda; Fernandes, Donald J; Mathew, Stanley; Chakrabarty, Jyothi; Devi, Elsa Sanatombi
Abstract: Aims and objectives: To evaluate the effectiveness of specialist nurse interventions in the care of women with breast cancer. Background: Nurses perform a crucial role in physical and psychosocial support of women with breast cancer. However, only few reviews have explored and discussed the roles and interventions carried out by specialised nurses in breast cancer care. Design: Systematic review based on PRISMA guidelines. Methods: A comprehensive literature search was conducted in PubMed, CINAHL, Scopus, Web of Science, Science Direct, Cochrane Library, IndMed and Shodhganga databases for articles published in English language from 1980 to 2018. Only RCTs were included. Quality assessment, data extraction and analysis were completed on all included studies. Results: Sixteen papers were assessed for methodological quality. Due to methodological heterogeneity of the papers, a meta‐analysis was not performed. The reviewers categorised the main outcomes under different domains like physical problems, psychological problems, patient satisfaction, patient needs, quality of life and cost data. Discussion: This review provides evidence on specialist nurses' role in breast cancer care. The methodological aspects of studies in this review vary in different aspects. More studies with rigorous scientific methods are needed to provide robust evidence on effectiveness of specialist nurses' role. Conclusion: Even though specialist nursing interventions can contribute to health outcomes of women with breast cancer, there is limited number of studies reported from developing countries. This warrants the need for specialist nurse interventions in breast cancer care from developing countries. Relevance to clinical practice: Offering a specialist nurse service helps the patients to meet their informational and educational needs, supportive care and coordination of care. Specialist breast nurse services can be integrated into hospital setting to improve patient care and treatment adherence.